'We (woman) [sic] actually don't think about it like that' : a narrative analysis of tears in the fabric of gendered experiences of aging following the loss of an intimate partner : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Williams, Sarah (Massey University, 2014)
Contemporary narratives about the ‘virtuousity’ of aging engage a dominant vision of independence and autonomy. Conducive to New Zealand’s neo–liberalist governing strategy, this vision generates moral trajectories around what constitutes ‘good citizenship’ in older age. This thesis considers women’s exclusion from such citizenship through their anticipated ‘dependent’ location in the social hierarchy. Following the literature on positive aging, the ongoing normalisation of the distinct and opposing binary of independence/dependence emerges through a gendered narrative that constrains women’s access to meaningful experiences of aging. Where the dominant cultural narrative of aging positions women as dependent and therefore deficient, the narrative is insufficient to appreciate the texture and complexity of women’s dependence experience. The text for analysis was generated through one to one interviews and two focus groups. This thesis represents a chorus of voices through women’s stories of losing an intimate partner to question gendered dependence narratives that render women’s experiences invisible in our disciplinary practices. The research asks how culturally produced narratives of dependency intersect with women’s experiences of gender and aging. This project specifically attends to the gendered cultural meaning of dependency on women’s experiences as they engage with reflexively transforming their loss. The analysis shows that women’s intersecting experiences of gender, loss and aging involve a diverse and textured experience of dependence, and intimate relationships were located as necessary to social relationships. Counter-narratives emerged to bring into view that women’s ‘dependency’ experience, configured and textured through meanings of intimacy embedded in the moral trajectory of femininity, locate women as responsible for the care of others and the success of their social spaces. As the women told their stories through a process of reflection, they began to challenge the meaning of their gendered social location through stories of political capacity, challenging the dominant narrative that marks relational responsibility as dependence. What emerged through the chorus of voices was how the women resisted the cultural narratives as they critically reflected on changes in their relationships. There were five themes that organised the analysis; the struggle over the meaning of intimacy and its relationship with dependency, questioning the meaning of change and choice in women’s social location as a process, personal agency and resilience, reflection on gendered social location through stories of political capacity, resistance as an embodied process of transformation to critically question cultural narratives of women’s position as virtuous agers. The research tells how women’s resistance is a textured relationship between public and private spaces and subversive acts as they negotiate the gendered social meanings of dependency complicated by a gendered subject location and its consequent moral trajectories. As they transform such spaces, resistance emerges through a recognition of themselves as agents of change. Resistance to the cultural narrative of dependency was countered through challenging the assumptions of sexual difference and the virtue of coupling. Taking up a position as ‘having’ social power enabled the women to live in new ways across multiple other relationships. It is through the navigation of intimacy that women experience the rich and dynamic contest of the boundaries around support and dependence, through which women experience relational negotiation. For this project, making visible this negotiation engages women’s diverse and dynamic experiences with ‘dependency’ as involving social power, and reveling in processes of transformation. The texture that gendered ‘dependency’ narratives can lend older women’s experience of reflexive transformation is the potential to challenge the constraints of gendered normality in a process through which women recognise their own experiences of dependence as enabling good citizenship. Creating space for the voices of women to emerge while simultaneously writing a thesis to produce a counter-narrative of resilience to produce new understandings of virtuous aging carries ethical responsibility. Creating ‘community’ conversations in the practice of this research project lead to the opening up of ‘discursive space’ capable of being inclusive of the complexity of women’s lives and experiences to provide a research experience for women that was transformative while retaining the integrity of the women's stories.